Local Innate Markers and Vaginal Microbiota Composition Are Influenced by Hormonal Cycle Phases - Adapen, Cindy; Réot, Louis; Nunez, Natalia; Cannou, Claude; Marlin, Romain; Lemaître, Julien; d’Agata, Léo; Gilson, Emmanuel; Ginoux, Eric; Le Grand, Roger; Nugeyre, Marie-Thérèse; Menu, Elisabeth (Frontiers in Immunology, 2022)
Background: The female reproductive tract (FRT) mucosa is the first line of defense against sexually transmitted infection (STI). FRT environmental factors, including immune-cell composition and the vaginal microbiota, interact with each other to modulate susceptibility to STIs. Moreover, the menstrual cycle induces important modifications within the FRT mucosa and affects these factors. Cynomolgus macaques are used as a study model for the pathogenesis and prophylaxis of STIs. In addition, it menstrual cycle and FRT morphology are similar to women. The cynomolgus macaque vaginal microbiota is highly diverse and similar to dysbiotic vaginal microbiota observed in women. However, the impact of the menstrual cycle on immune markers and the vaginal microbiota in female cynomolgus macaques is unknown. We thus conducted a longitudinal study covering three menstrual cycles in cynomolgus macaques. The evolution of the composition of the vaginal microbiota and inflammation (cytokine/chemokine profile and neutrophil phenotype) in the FRT and blood was determined throughout the menstrual cycle. Results: Cervicovaginal cytokine/chemokine concentrations were affected by the menstrual cycle, with a peak of production during menstruation. We observed three main cervicovaginal neutrophil subpopulations: CD11bhigh CD101+ CD10+ CD32a+, CD11bhigh CD101+ CD10- CD32a+, and CD11blow CD101- CD10- CD32a-, of which the proportion varied during the menstrual cycle. During menstruation, there was an increase in the CD11bhigh CD101+ CD10+ CD32a+ subset of neutrophils, which expressed higher levels of CD62L. Various bacterial taxa in the vaginal microbiota showed differential abundance depending on the phase of the menstrual cycle. Compilation of the factors that vary according to hormonal phase showed the clustering of samples collected during menstruation, characterized by a high concentration of cytokines and an elevated abundance of the CD11bhigh CD101+ CD10+ CD32a+ CD62L+ neutrophil subpopulation. Conclusions: We show a significant impact of menstruation on the local environment (cytokine production, neutrophil phenotype, and vaginal microbiota composition) in female cynomolgus macaques. Menstruation triggers increased production of cytokines and the recruitment of mature/activated neutrophils from the blood to the FRT. These results support the need to monitor the menstrual cycle and a longitudinal sampling schedule for further studies in female animals and/or women focusing on the mucosal FRT environment.